Managing Know-How - Lee, Deishin; Van den Steen, Eric (Management Science, 2010)
We study how firms can use a knowledge management system to optimally leverage employee-generated know-how. In particular, we consider the following practical strategic questions for the manager of a knowledge-intensive firm: Should her firm develop a formal knowledge system? And if so, how should it be managed, particularly in terms of what information to record? We find that firms benefit more from a knowledge system when they are larger, face the same issues more frequently, have higher turnover, and face problems about which there is less general knowledge. In terms of what information to record, a key insight is that recording moderately successful practices can be counterproductive, because doing so may inefficiently reduce employees' incentives to experiment. This “strong-form competency trap” forces firms into an exploration–exploitation trade-off. Firms that value a knowledge system most should also be most selective in recording information. We further find that recording successes is more valuable than recording failures, which supports firms' focus on best practice. Beyond these main principles, we also show that it may be optimal to disseminate know-how on a plant level but not on a firm level, and that recording backup solutions is most valuable at medium levels of environmental change.